Risk factors associated with musculoskeletal pain in undergraduate students: a systematic literature review - Barrenachea Arakaki, Jimena Saori (2024)
Background: Musculoskeletal pain is a problem many workers suffer worldwide, triggering more severe diseases and decreased quality of life. In addition, several studies have shown that university students are no strangers to suffering from these pains, and it is known that more and more of them report pains in different body areas. Therefore, this study aims to determine undergraduate students' risk factors associated with musculoskeletal pain. Methodology: A systematic literature review followed the process proposed in the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) statement. The searches were conducted in Scopus, Web of Science, and Scielo, obtaining 3311 articles, of which 89 were included for this review. Results: Of the 38 possible risk factors, five factors were evaluated, and it was found that physical activity, time in front of a screen, and having a history or family history of musculoskeletal pain/trauma do represent a risk factor, while no association was found for gender and time in a sedentary position. Conclusion: Three risk factors for the presence of musculoskeletal pain were found in the review. In turn, there is little existing literature on COVID-19 and its effect on the presence of musculoskeletal pain and associated risk factors in undergraduate students, so it is advisable to conduct further research in this context.